Photosynthesis improvement and the relationship between photosynthetic pigments and primary metabolism in tomato leaves - Pereira, Auderlan de Macena (2019)
Photosynthesis is responsible for the primary productivity and maintenance of life on the planet, boosting biological activity and contributing to the maintenance of the environment. Traditional crop improvement has been sufficient to keep up with the growing demand for food. However, advances in this area have not focused on photosynthesis, per se, but on fixed carbon partitioning. In the near future other approaches must be used to meet the increasing demand. Thus, several paths may be followed, from improving metabolic pathways related to CO2 fixation, inclusion of metabolic mechanisms from other species and improvements in energy uptake by plants. For the use of energy, it must be first absorbed by photosynthetic pigments, transferring it in the form of excitation energy to the reaction centers where it is converted into biochemical energy. The carbon products fixed in photosynthesis are further used as energy source and building blocks by several metabolic routes. Photosynthetic pigments are also produced from carbon skeletons provided by the primary metabolism, and therefore changes in carbon flow to pigment biosynthesis will likely lead to consequences in the parts of metabolism. In this context, the main goals of this work were: (i) to review and present recent advances related to the improvement of photosynthesis in plants, showing promising advances in the field of plant photosynthesis optimization, with well-established future directions; (ii) to investigate how high pigment mutations (hp1 and hp2) influence tomato metabolic machinery and how these plants adjust themselves to different light conditions; and (iii) to increase our understanding of how mutations that alter carotenoid biosynthesis [namely crimson (old gold-og), Delta carotene (Del) and tangerine (t)] affect the metabolic machinery of tomato plants. Regarding mutations associated with pigment biosynthesis, the data obtained clearly show that extensive metabolic reprogramming occurs allowing plants to withstand changes in the biosynthesis of photosynthetic pigments. Although the mutants were characterized by higher net photosynthesis (A), lower stomatal limitation, higher Vcmax and anatomical modifications that favor photosynthesis, we found that carbohydrate levels are not increased. Another conspicuous feature is that shading minimizes the above differences between mutants and WT, or even fully reversed this in the case of certain metabolites. We further observed that mutations og, Del and t did not greatly affect vegetative growth, leaf anatomy and gas exchange parameters. However, an exquisite metabolic reprogramming was recorded. Taken together, our results show that despite minor impacts on growth and gas exchange, carbon flux is extensively affected, leading to adjustments in tomato metabolism to support changes in carotenoid biosynthesis. It is important to mention that such metabolic alterations seems to have little impacts on growth parameters, although yield is strongly affected. Our results also open novel research avenues, indicating new possibilities for better understanding the relationship between photosynthetic pigments and plant metabolism, as well as the enhancement of photosynthesis.